Penentuan Jumlah Sumber Daya Manusia (SDM) di Bank XYZ dengan Menggunakan Pemodelan Simulasi - Kusferyano, Bonfilio Elyan; The, Jin Ai; Purnama, Ign. Luddy Indra (Universitas Katolik Parahyangan, 2024)
In 2020 Covid-19 Pandemic strikes the whole country. It forces Organization to change their work habits from Work from Office (WFO) to Work from Home (WFH). It is also triggered by Indonesia Government policy to keep Social Distancing and start Work from Home (WFH). Bank XYZ response by change their working policy to allow employee Work from Office and Work from Home (Hybrid). Then each employee has a different work schedule every week based on their position and Line Manager discretion. Change of amount employee who work from office affects its performance obviously, especially operational function in this case HR Data Management Function. Bank XYZ has not make a further assessment, planning or working simulation about the optimal number of WFO employees yet. By direct observation, processing time data measurement, and memo arrival time data measurement, we make a model simulation based on Arena Software to find most suggested number of WFO employee. The simulation result shows that 7 employees is the best employee number consisting of 1 Team Lead, 1 Analyst, 1 Analyst Assistant, 2 Administrator and 2 Archive Personnel. This number is less than existing employee number before, 14 employees.